Managers at work. - Wolff, Michael F. (Research management (Now: research technology management))
Michael F. Wolff interviews Edward F. McQuarrie for advice on Making Customer Visits Pay. Followed by Charles J. Bishop on Creating a 'Sense of Urgency.'